The Role of Proximity in Resources Exchanged by Incubatees of Biopartner Center Leiden, the Netherlands - Schutjens, Veronique; Kruger, Maarten (European Spatial Research and Policy, 2020)
Subject literature assumes that spatial proximity stimulates collaboration in thematic clusters. However, even in micro-scale settings, resource exchange is rare or entails only tangible resources. We empirically unravel how specific proximity indicators relate to the types of resources exchanged in incubatees’ business relationships. Based on 118 business relationships of incubatees, we conclude that on the micro-scale of an incubator, site proximity to another incubatee has a limited relation and geographical proximity to business partners outside the incubator has no relation to the types of resources exchanged. For the latter business relationships, personal similarity positively relates to the exchange of specific business knowledge resources.